2019
DOI: 10.1002/aoc.4860
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of Ni (II), Cu (II), Fe (II) and Fe3O4 nanoparticle complexes with tetraaza macrocyclic Schiff base ligand for antimicrobial activity and cytotoxic activity against cancer and normal cells

Abstract: This work describes a simple synthesis of complexes of the type [M(C32H28N4)Cl2], where M = Ni (II), Cu (II) and Fe (II) and a novel complex of magnetite nanoparticle (Fe3O4NP) inside (INS) tetraaza macrocyclic Schiff base ligand (C32H28N4): [Fe3O4NP‐INS‐(C32H28N4)], which was prepared by using a novel co‐precipitation method of coordinated ferric ion (Fe3+) in the complex [Fe(C32H28N4)Cl2] under mild conditions. The synthesized compounds were characterized and compared with a various physic‐chemical technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…[44,45] Mn(II), Co(II), Cu(II), Zn(II), and Cd(II) complexes were nonelectrolytes, cofirming that all the chlorides in nonelectrolytic complexes were part of the coordination sphere. [46,47] From previous studies, Khalil et al (2021) was prepared metal complexes of naphthalene-1,8-diamine derivatives and measured their molar conductance, which showed that all complexes were electrolytes with value between 67-86 Ω À1 mol À1 cm 2 , whereas Zn(II) complex was nonelectrolyte with value <50 Ω À1 mol À1 cm 2 . These results confirmed our explanation about the results of conductivity.…”
Section: Molar Conductivity Measurementsmentioning
confidence: 99%
“…[44,45] Mn(II), Co(II), Cu(II), Zn(II), and Cd(II) complexes were nonelectrolytes, cofirming that all the chlorides in nonelectrolytic complexes were part of the coordination sphere. [46,47] From previous studies, Khalil et al (2021) was prepared metal complexes of naphthalene-1,8-diamine derivatives and measured their molar conductance, which showed that all complexes were electrolytes with value between 67-86 Ω À1 mol À1 cm 2 , whereas Zn(II) complex was nonelectrolyte with value <50 Ω À1 mol À1 cm 2 . These results confirmed our explanation about the results of conductivity.…”
Section: Molar Conductivity Measurementsmentioning
confidence: 99%
“…In fact, macrocyclic Schiff bases are particularly important in macrocyclic chemistry because of their exible synthesis, their selectivity, and even their ability to stabilize many metals in various oxidation states [12][13][14][15][16]. However, a huge number of tetraaza macrocyclic (N 4 ) metal complexes show interesting biological activities such as antifungal [17,18], antibacterial [19][20][21], antimicrobial [22][23][24][25] and anticancer [11,26,27] effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, the co-precipitation method usually shows the di culty to control nanoparticle size and distribution size due to the strong dipole-dipole interactions which lead to the formation of Fe 3 O 4 NPs aggregated. So, the deterioration of magnetic proprieties [19,47].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the co-precipitation method usually shows the di culty to control nanoparticle size and distribution size due to the strong dipole-dipole interactions which lead to the formation of Fe 3 O 4 NPs aggregated. So, the deterioration of magnetic proprieties [19,47].…”
Section: Introductionmentioning
confidence: 99%